The impact of an extended nucleobase-2′-deoxyribose linker in the biophysical and biological properties of oligonucleotides. Issue 16 (31st January 2017) - Carnero, Alejandro; Pérez-Rentero, Sónia; Alagia, Adele; Aviñó, Anna; Sanghvi, Yogesh S.; Fernández, Susana; Ferrero, Miguel; Eritja, Ramon
Abstract : The introduction of a novel thymine derivative at the 3′-end of the sense strand generates more potent and selective siRNAs. Abstract : Interest in artificial DNA mimetics has been triggered by the widespread applications of nucleic acids as they are useful tools for modulation of the biophysical and biological properties of oligonucleotides. In this article, we describe the synthesis and properties of a novel thymine derivative (T*) containing an extended linker between the thymine nucleobase and the 2′-deoxyribose moiety. The modified 2′-deoxyribosyl derivative was prepared via coupling of a functionalized nucleobase to the amino group of 1-aminomethyl-2-deoxyribose, which was synthesized starting from an easily accessible cyano sugar available on a large-scale. Corresponding phosphoramidite and succinyl derivatives have also been incorporated into oligonucleotides at predetermined sites and defined internucleotidic motifs using the solid-phase synthesis approach. This derivative pairs equally well with adenine and guanine and it can be safely introduced at the 3′-end of the siRNAs to generate potent inhibitors of gene expression by the RNA interference mechanism.